Family Conflict, Stressful Family Situations and Aggression in Adolescence. The Role of Hostility - Vegas, María Isabel (2024)
Objective. To analyze the relationship between family conflicts and other stressful family situations with aggression in adolescents. Method. A total of 1193 Spanish adolescents aged 14 to 18 years were selected from 51 educational centers or juvenile centers. The Buss and Perry Aggression Questionnaire –BPAQ– was used. Results. Family conflict and poor school grades were risk factors for physical aggression, anger and hostility; the absence of parental figures was a risk factor for anger and hostility; and economic or work-related difficulties were a risk factor for hostility. Hostility correlated positively with all of the stressful family factors analyzed and emerged as a variable simultaneously linked to the increase in family conflicts, family stress, and adolescent physical aggression. Intervention proposals are suggested.